2016
DOI: 10.1177/1526602816651424
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenting With Proximal Embolic Protection via a Transradial or Transbrachial Approach

Abstract: CAS with proximal protection via a TR or TB approach is a feasible, safe, and effective technique with a low rate of vascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
(57 reference statements)
0
26
0
2
Order By: Relevance
“…The proximal EPD is a protection way preferred in the patients with high risk plaque (recent symptomatic, ulcereous plague, heterogeneous and lipid rich plague) and intramural hemorrhage and intraluminal thrombus, as there is no need to pass through the stenosis area, although the placement is more difficult comparing to distal EPD placement (2,4). Although there are evidences that proximal EPD protects the brain against the microembolization more than distal EPD (5), this difference cannot be identified clearly in meta-analyzes (3).…”
Section: Discussionmentioning
confidence: 99%
“…The proximal EPD is a protection way preferred in the patients with high risk plaque (recent symptomatic, ulcereous plague, heterogeneous and lipid rich plague) and intramural hemorrhage and intraluminal thrombus, as there is no need to pass through the stenosis area, although the placement is more difficult comparing to distal EPD placement (2,4). Although there are evidences that proximal EPD protects the brain against the microembolization more than distal EPD (5), this difference cannot be identified clearly in meta-analyzes (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have experienced only two cases, and a larger number of cases must be analyzed to evaluate whether our method is more useful than in previous studies. [10][11][12] As indicated in this study, pigtail catheters may be useful in patients with a sharp angle between the subclavian artery and the common carotid artery, but the following limitation is suggested: in case 2, a sharp-angle-mediated approach reduced guidewire operability, and we had to use a torque device to improve the operability. In this study, the use of a torque device improved the operability.…”
Section: Disclosure Statementmentioning
confidence: 93%
“…[10][11][12] Essentially, pigtail catheters themselves were not designed for usage for peripheral blood vessel, and their flexibility and trackability are less marked than those of standard catheters. On the other hand, advantages and disadvantages are two sides of the same coin.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…A study from Italy reported the outcomes of 214 patients undergoing CAS via a transradial ( n = 154) or a transbrachial ( n = 60) approach with either the Mo.Ma proximal protection ( n = 61) or the distal filter protection ( n = 163)[36]. As a result of technical difficulties in catheterizing the target vessel, crossover to a femoral approach was required in 11 of 153 (7.1%) filter patients, but only in 1 of the 61 (1.6%) Mo.Ma patients.…”
Section: Head-to-head Comparison/combination Of Strategiesmentioning
confidence: 99%
“…After a mean follow-up of 8.1 ± 7.5 mo, chronic radial artery occlusion was detected by Doppler ultrasound in 2 of the 30 (6.6%) Mo.Ma patients and by clinical assessment in 4 of 124 (3.2%) filter patients ( P = 0.25). The conclusion reached was that CAS with proximal protection via a transradial or a transbrachial approach is a safe, feasible and effective technique with low rate of vascular complications[36]. …”
Section: Head-to-head Comparison/combination Of Strategiesmentioning
confidence: 99%